A quasi-experimental eye-tracking study investigating the relationship between professional vision and the dispositions for inclusive teaching - Grub, Ann-Sophie; Selisko, Tom Jannick; Lewalter, Doris; Biermann, Antje (Frontiers in Education, 2025)
Inclusive education aims to provide equal learning opportunities for all students by addressing their diverse needs. Teachers must identify and respond to the physical and psychological requirements of individual learners to deliver adaptive and differentiated instruction. Professional vision plays a critical role in managing inclusive classrooms, which demands more nuanced approaches than homogeneous groups. This study explores key factors that influence professional vision for inclusive teaching, focusing on pedagogical knowledge, attitudes, and self-efficacy. Attitudes toward inclusive education influence a teacher's willingness to implement inclusive practices, while self-efficacy reflects confidence in managing diverse classrooms. The study analyzed professional vision among 80 pre-service teachers using eye-tracking technology. Participants were presented with four teaching video vignettes designed to assess student orientation (fixation count and duration), and verbal recognition performance of inclusive events. Predictors included pedagogical knowledge, attitudes toward inclusive education, and self-efficacy beliefs on adaptive teaching. The results showed that attitudes, self-efficacy, and pedagogical knowledge could not significantly predict total fixation duration or fixation count. Similarly, these predictors were unrelated to the verbal recognition performance of critical incidents, even when analyzed at the video level. The study emphasizes the need to enhance teacher training to prepare pre-service teachers to identify critical classroom situations. Such improvements aim to foster professional vision and adaptive teaching strategies in inclusive education.